Transformational Leadership Influence on Employee Performance: A Proposed Study among Palestinian Central Municipalities Employees - Omar Jamil Ahmed Muqedi; Khairunneezam Mohd Noor (Asian Scholars Network (ASNet), 2024)
Non-Indexed Publication